CURPH Interview 73-M with a 1956 Hungarian Refugee: 34 Years Old, Male, Translator in the Hungarian Foreign Service - Columbia University School of International Affairs
Transcript of an interview conducted as part of the Columbia University Research Project on Hungary (CURPH) in the wake of the 1956 Hungarian Revolution. Place of Interview: New York (N.Y.) Date of Interview: 20 February 1957 Interview ID: 73-M Interview Type: Preliminary Covers topics related to everyday life and politics in Hungary between the end of World War II and the 1956 Hungarian Revolution. The document notes that the interviewee had the following characteristics: Education level: University Occupation: Translator, Hungarian Foreign Service Religious preference: Roman Catholic Place of residence before emigration: Budapest Date of departure: 22 November 1956